KONTRIBUSI KETERAMPILAN MENYIMAK TEKS LAPORAN HASIL OBSERVASI TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 2 PARIAMAN - Salmeliani, Rina; Nursaid, Nursaid; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ This article was written to describe the contribution of listening skill of observation report texts to the skill of writing the text of the result of observation of the seventh grade students of SMP Negeri 2 Pariaman. This research is a quantitative research with descriptive method. The sample in this study amounted to 38 people. The data of this research is score of skill test result listening the observation report text. Based on data analysis and discussion, the following three things are obtained. First, the skill of writing the text of the result of observation of the seventh grade students of SMP Negeri 2 Pariaman is in good qualification (80,15). Second, the skill of listening to the text of the result of observation of the seventh grade students of SMP Negeri 2 Pariaman is in good qualification (82.20). Third, the listening skill of the observation report has 31,03% contribution to the writing skill of the observation report of VII students of SMP Negeri 2 Pariaman and the rest (68,97%) influenced by other factors not examined in this research.Â Kata kunci: kontibusi, menyimak, menulis, teks laporan hasil observasi